OXYGEN CONSUMPTION IN RELATION TO SPONTANEOUS ACTIVITY AND AMBIENT OXYGEN IN FIVE MARINE TELEOSTS - Hamsa, K M S Ameer; Kutty, M N (Indian Journal of Fisheries, 2011)
Some metabolic adaptations of 5 species of South Indian marine teleosts, o namely Caranx carangus (Bloch), Chorintmus lysan (Forskal), Chanos chanos o (Forskal), Synagris furcosus (Day) and Gerres lucidus (Day) were studied. The fishes were acclimated to and tested at an average temperature of 30Â°C and 357^^ salinity